METODOLOGI FEMINIS: DESAIN PENELITIAN TERHADAP PERCERAIAN - Muhayani, MPP., Ulfah (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Since its emergence in 1980s, Feminist Research Methodology has become a legitimate, relevant and popular research model. Its quality, and the validity of its findings are beyond contention, and over the years it has produced a significant output that has provided guidelines for policies central to modern society. For its founders and developers, Feminist Research Methodology is designed to study the social conditions of women in a sexist, ‘malestream’ and patriarchal society. Yet, this methodology is rarely used in studies dealing with women problems in Indonesia. Thus paper aims discuss FMR and its application of the model in divorce studies.